1997
DOI: 10.1111/j.1600-0765.1997.tb01399.x
|View full text |Cite
|
Sign up to set email alerts
|

Underlying mechanisms at the bone‐surface interface during regeneration

Abstract: The goal of regenerative therapy around teeth and implants is to create a suitable environment in which the natural biological potential for functional regeneration of periodontal ligament and/or bone can be maximized. In order for the regenerative process to be successful, the following factors must be addressed: prevention of acute inflammation from bacteria, mechanical stability of the wound, creation and maintenance of blood clot-filled space, isolation of the regenerative space from undesirable competing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
69
0
9

Year Published

2000
2000
2023
2023

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 112 publications
(80 citation statements)
references
References 26 publications
2
69
0
9
Order By: Relevance
“…The principal mechanisms underlying the healing around implants are comparable to those of fracture healing (Schenk & Herrmann 1984;Gross 1988;Plenk & Zitter 1996;Overgaard 2000), although this view has triggered much debate since some authors have suggested that the presence of an implant induces a different healing mode (Schwartz et al 1997;Steflik et al 1998).…”
Section: Bone Regeneration (A ) Biology Of Bone Regenerationmentioning
confidence: 93%
“…The principal mechanisms underlying the healing around implants are comparable to those of fracture healing (Schenk & Herrmann 1984;Gross 1988;Plenk & Zitter 1996;Overgaard 2000), although this view has triggered much debate since some authors have suggested that the presence of an implant induces a different healing mode (Schwartz et al 1997;Steflik et al 1998).…”
Section: Bone Regeneration (A ) Biology Of Bone Regenerationmentioning
confidence: 93%
“…Surface roughness not only increases surface area but also affects cell morphology and increases osteoblastic differentiation, bone formation, and bone remodeling (Schwartz et al 1997;Wennerberg and Albrektsson 2009).osteoblastic differentiation and maturation (Olivares-Navarrete, Hyzy, Hutton, et al 2010) and implant osseointegration .…”
Section: Surface Roughnessmentioning
confidence: 99%
“…In contrast to Hwang et al, 3 the removal torque and BIC were significantly increased in 8 weeks of resettlement. It is considered that the implants with surface treatment support the continuous bone formation as the study of Schwartz et al, 11 which suggested that the rough surfaces of the implants with surface treatment stimulate proliferation and differentiation of osteoblasts to contribute preferable bone formation.…”
Section: Discussionmentioning
confidence: 99%